On the history of classical studies in the Imperial Kazan University: the department of Roman literature in the 1880s — 1890s - Natalia Almazova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article deals with the history of classical studies in the Imperial Kazan' University in 1880-1890s, which was connected with the activities of two professors at the Chair of the Roman Literature, Darius Naguevskiy (1845-1918) and Stanislaw Opatskiy (1847-?, after 1900). According to the students of the history of classical research at the Kazan' University in the late 19th century, studies in the Roman history and literature were represented there in this period at a considerably lower scale than those of the Ancient Greek history, language and literature. One should ask why the Kazan' University failed to shape the specific tradition of studying the Roman antiquity, in spite of its employing throughout the 19th century prominent Romanists (N.M. Blagoveshchenskiy, V.I. Modestov). Besides the Ministry of Public Enlightenment was obviously interested in promoting the courses of the Chair of the Roman Literature, as it appointed for it with a brief interval two Classical philologists specialized in Latin poetry and prose, Dr. Lit. D. Naguevskiy in 1883 and M. Lit. S. Opatskiy in 1885. The article attempts to answer this question taking into account both essential and personal factors of the problem, the latter being the individual features of the two professors and their conflicts.